Constraints to Exclusive Breastfeeding Practice Among Lactating Mothers in Omala LGA of Kogi State: Implications for Protection Against Infants’ Reemerging Infections and Maternal Health Problems - Iwuagwu, Tochi Emmanuel; Ene , Osmond Chukwuemeka (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The study examined constraints to exclusive breastfeeding practice among lactating mothers in Omala LGA of Kogi State and its implications for infants’ protection against reemerging infections and maternal health problems. Three research questions and two null hypotheses guided the study. The study adopted the descriptive survey research design. The sample was 322 lactating mothers selected from a population of 3,320 through multi-stage sampling procedure. A valid and reliable questionnaire was used for data collection. Percentages were used to answer the research questions while chi-square statistic was used to test the null hypotheses at .05 level of significance. Results of the study among others indicated that a high proportion of lactating mothers (61.5%) reported maternal occupation; a moderate proportion (47.7%) reported conflicting positions from significant others; while low proportion (22.4%; 38.9%; 25%) reported maternal health and lactation problems and poor nutrition as constraints to EBF practice respectively. Lactating mothers with secondary education (71.7%) reported slightly higher proportion of constraints to EBF practice than those with primary education (66.1%), tertiary education (59.2%), and no formal education (44.7%). Lactating mothers aged 15-30 years (75.9%) reported higher proportion of constraints to EBF practice more than those aged 45 years or above (57.3%), and 31-44 years (52.4%). There were significant differences in the constraints to EBF practice among lactating mothers based on level of education and age. Based on the findings, recommendations were made among which is that Government, Non-Governmental organizations and other allied health professionals and social organization such as churches, mosques should carryout enlightenment campaign programmes that could correct the misconceptions and fallacies about EBF that constraint mothers from effectively adopting it.